Differences in Data Protection Systems in Indonesia And Singapore - Rizki Rizki; Elfrida Ratnawati Gultom (Indonesian Journal of Law and Policy Studies, 2022)
The Indonesian Personal Data Protection Law that was recently legalized by the government aims to protect people’s personal data, to provide a sense of security and provide legal certainty to its users, but there are several weaknesses that are considered not to strengthen the purpose of the act, where there are no phrases in confirmation of individuals who have data, this is different from Singapore, before data usage, Singapore confirmed the purpose of using the data against the owner of the data and there were strict sanctions and a special institution in supervising the use of personal data.